2020 IEEE Latin-American Conference on Communications (LATINCOM) 2020
DOI: 10.1109/latincom50620.2020.9282312
|View full text |Cite
|
Sign up to set email alerts
|

Multimetric Online Intrusion Detection in Software-Defined Wireless Sensor Networks

Abstract: Software-defined wireless sensor networks have attracted considerable attention in recent years as they simplify the network management and provide the framework to automate infrastructure sharing. On the other hand, the centralization and planes' separation can turn SDNs vulnerable to new types of denial of service attacks. Existing intrusion detection approaches are not in general suitable for restricted networks or do not achieve optimal detection rates. This work aims at fulfilling both requirements by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In case of FNI attack, the detector monitoring the data packets delivery rate was triggered first in 100% of the events, as shown in Figure 29b. These results showed that there is evidence to support the hypothesis drawn up in our previous works about the relation metric / attack (SEGURA et al, 2020).…”
Section: Optimizing 𝑚 and 𝛾supporting
confidence: 89%
See 4 more Smart Citations
“…In case of FNI attack, the detector monitoring the data packets delivery rate was triggered first in 100% of the events, as shown in Figure 29b. These results showed that there is evidence to support the hypothesis drawn up in our previous works about the relation metric / attack (SEGURA et al, 2020).…”
Section: Optimizing 𝑚 and 𝛾supporting
confidence: 89%
“…Next, the anomaly detection algorithm was implemented. We chose to use change point analysis since it fulfills the lightweight criteria and the previous evaluation (SEGURA et al, 2020) showed detection performance results similar to other works in the literature using ML techniques, among others. However, our proposal is independent of the anomaly detection technique while it is lightweight enough to fit and run in simple WSN or IoT devices.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations